Correction: Robust radiogenomics approach to the identification of EGFR mutations among patients with NSCLC from three different countries using topologically invariant Betti numbers. - Kenta Ninomiya; Hidetaka Arimura; Wai Yee Chan; Kentaro Tanaka; Shinichi Mizuno; Nadia Fareeda Muhammad Gowdh; Nur Adura Yaakup; Chong-Kin Liam; Chee-Shee Chai; Kwan Hoong Ng (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0244354.].